In-vitro evaluation of anti-factor IXa aptamer on thrombin generation, clotting time, and viscoelastometry - Tanaka, Kenichi A.; Szlam, Fania; Rusconi, Christopher P.; Levy, Jerrold H. (Thrombosis and Haemostasis, 2009)
The REG1 system consists of factor IXa inhibitor, RB006, an ap-tamer-based anticoagulant and its antidote, RB007. The optimal use of RB006 can be facilitated by understanding its effect on the formation of thrombin and fibrin, and other standard tests of coagulation. Blood from consented volunteers was drawn into 3.2% citrate (9:1 v/v) and either used immediately or centrifuged to obtain platelet-poor plasma. Increasing concentrations of ap-tamer (6–24 μg/ml) alone or in combination with heparin (0.1 U/ml) or lepirudin (0.2 μg/ml) were added to blood and plasma samples. Activated clotting times (ACT+, low range-ACT), thrombelastometry (ROTEM™) or thrombelastography (TEG®) were performed in recalcified whole blood samples. Thrombin generation, prothrombin time (PT) and activated partial thromboplastin time (aPTT) were performed in plasma samples. To some samples the antidote RB007 was added to neutralise the anticoagulation activity of RB006. In all experiment the ratio of RB006 to RB007 was kept 1:2. RB006 dose-dependently prolonged aPTT and low range-ACT, but, as expected, had no effect on PT. RB006 prolonged the lag time and decreased the peak of Actin-triggered thrombin generation. Thrombin-activated TEG demonstrated that RB006 decreases the rate of clot formation. These effects were potentiated when RB006 was combined with heparin or lepirudin. In all experiments RB007 reversed the effects of RB006 back to baseline. In conclusion, RB006 inhibits thrombin generation and clot formation in a concentration-dependent manner. It is feasible to monitor RB006 and its reversal with RB007 using aPTT, low range-ACT, and thrombin-activated TEG.
Keywords: Anticoagulation; aptamer; factor IXa inhibition; thrombin inhibition